2006
DOI: 10.5194/acp-6-4079-2006
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric sulphuric acid and aerosol formation: implications from atmospheric measurements for nucleation and early growth mechanisms

Abstract: Abstract.We have investigated the formation and early growth of atmospheric secondary aerosol particles building on atmospheric measurements. The measurements were part of the QUEST 2 campaign which took place in spring 2003 in Hyytiälä (Finland). During the campaign numerous aerosol particle formation events occurred of which 15 were accompanied by gaseous sulphuric acid measurements. Our detailed analysis of these 15 events is focussed on nucleation and early growth (to a diameter of 3 nm) of fresh particles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
579
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 462 publications
(619 citation statements)
references
References 49 publications
37
579
3
Order By: Relevance
“…By rearranging the terms, and denoting the first term on the right hand side of Eq. (2) by J 3 , the previous studies (Sihto et al, 2006;Paasonen et al, 2009) gave the Eq. (3) to calculate the particle formation rate at 3 nm:…”
Section: Particle Formation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…By rearranging the terms, and denoting the first term on the right hand side of Eq. (2) by J 3 , the previous studies (Sihto et al, 2006;Paasonen et al, 2009) gave the Eq. (3) to calculate the particle formation rate at 3 nm:…”
Section: Particle Formation Ratesmentioning
confidence: 99%
“…In order to investigate the role of sulfuric acid in the nucleation process, based on recent observations the relationship between observed nucleation rates and ambient gaseous sulfuric acid concentrations with an exponent between 1 (J =A × [H 2 SO 4 ]) and 2 (J =K × [H 2 SO 4 ] 2 ) have been reported (Sihto et al, 2006;Riipinen et al, 2007;Boy et al, 2008;Kuang et al, 2008;Nieminen et al, 2009;Paasonen et al, 2009). In these publications the authors pointed out that the activation and kinetic nucleation maybe the potential formation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient and laboratory studies have shown that sulfuric acid participates in the first steps of new particle formation (Weber et al, 1996;Sihto et al, 2006;Riipinen et al, 2007;Kuang et al, 2008;Sipilä et al, 2010;Vehkamäki and Riipinen, 2012;Kulmala et al, 2013), but sulfuric acid condensation is not enough to reproduce particle growth rates observed in the ambient conditions (Kuang et al, 2010;Sipilä et al, 2010;Pierce et al, 2011Pierce et al, , 2012Riipinen et al, 2011Riipinen et al, , 2012Kulmala et al, 2013). Therefore other compounds, e.g., organics or ammonia/amines, are expected to be important in the early growth of freshly nucleated particles (O'Dowd et al, 2002;Smith et al, 2005Smith et al, , 2008Pierce et al, 2011;Riipinen et al, 2012;Vehkamäki and Riipinen, 2012;Kulmala et al, 2013).…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 99%
“…However, the uncertainty in this number is large and it is still unclear which vapors are participating in the formation of the critical nucleus under certain conditions and which species contribute to its early growth. In most cases atmospheric boundary layer nucleation events cannot be explained solely by the binary system of sulfuric acid and water, although a correlation with the sulfuric acid concentration is generally observed 2,3 . Consequently, ternary vapors need to participate and it has been suggested that ammonia plays a key role 4,5 .…”
Section: Ternary H 2 So 4 -H 2 O-dimethylamine Nucleationmentioning
confidence: 99%